2000
DOI: 10.1117/1.1312647
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of direct milling of micro-optical elements with continuous relief on a substrate by focused ion beam technology

Abstract: A novel method of manufacturing micro-optical elements with continuous relief by focused ion beam (FIB) is described in detail. Microfabrication of diffractive optical elements (DOEs) with feature sizes as small as the submicronmeter range is realized in this way. Making use of direct milling by FIBs, the microstructure on any substrate (metal and nonmetal) and the mold used for micro-optical element replication are realized easily without any other procedures. The DOEs are duplicated by hot-embossing with rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The corresponding normalized pixel spacing (p s /σ ) is 0.15, which is much less than 1 and should yield a very smooth ion flux, as discussed earlier. Yongqi and Ngoi (2000) also reported that the surface and dimensional quality of the optical elements is dependent on the beam size; the smaller the beam size, the better the quality. Microlens arrays have applications in optical interconnects, multiple spot scanning microscopy, laser-to-fiber coupling, and numerous other areas in which geometrically precise arrays are required.…”
Section: Annular Patternsmentioning
confidence: 97%
See 1 more Smart Citation
“…The corresponding normalized pixel spacing (p s /σ ) is 0.15, which is much less than 1 and should yield a very smooth ion flux, as discussed earlier. Yongqi and Ngoi (2000) also reported that the surface and dimensional quality of the optical elements is dependent on the beam size; the smaller the beam size, the better the quality. Microlens arrays have applications in optical interconnects, multiple spot scanning microscopy, laser-to-fiber coupling, and numerous other areas in which geometrically precise arrays are required.…”
Section: Annular Patternsmentioning
confidence: 97%
“…In milling, both raster and serpentine scans are popular. For example, Yamaguchi et al (1985), Yamaguchi and Nishikawa (1995), Yongqi and Ngoi (2000) and Tseng et al (2002) adopted a raster scan in their research, while Ishitani et al (1991), Young et al (1993) and Steckl and Chyr (1999) used a serpentine scan to regulate the beam movement. No noticeable impacts on the resulting milled structures have been reported by just changing the scan from raster to serpentine or vice versa.…”
Section: Raster and Serpentine Scansmentioning
confidence: 99%